Split application of nitrogen: A strategy for improving fodder yield and quality in Kharif sorghum - Patel, A J; Patel, H K; Rathod , P H; Raval, C H; Parmar, D K; Chavda, Krishna; Kurkutiya, S R (Plant Science Today, 2025)
A field experiment was carried out during kharif season of 2023 at MFRS, AAU, Anand-388 110, Gujarat to evaluate the “Effect of split application of nitrogen levels on kharif fodder sorghum”. The experiment was laid out in randomized block design (Factorial) with three replications. There were 12 treatment combinations which included four nitrogen levels. According to results, application of 120 kg N/ha (N3) was reported significantly higher plant height at 45 DAS and at harvest, number of leaves per plant and leaf stem ratio, maximum green forage yield (356.14 q/ha), dry matter yield (104.49 q/ha), crude protein yield (5.70 q/ha) and dry matter content, ash content and lower acid detergent fiber (ADF) and neutral detergent fiber (NDF) content and higher nutrient content and uptake by fodder sorghum over other level of nitrogen. Response of nitrogen on plant population at 15 DAS, plant height at 30 DAS, available phosphorus in soil and phosphorus content in plant was found non-significant. Split application of nitrogen treatment S3 (25 % N at Basal + 37.5 % N at 30 DAS + 37.5 % N at 45 DAS) reported significant response on growth parameters like periodical plant height, numbers of leaves per plant, leaf stem ratio and yield and quality parameters like green fodder yield, dry matter yield, dry matter content, crude protein content, crude protein yield, ADF, NDF, ash content and nutrient content and uptake by fodder sorghum as compared to rest of treatments. Interaction effect between N3S3 (120 kg N/ha applied as 25 % N at Basal + 37.5 % N at 30 DAS + 37.5 % N at 45 DAS) exhibited maximum green fodder yield (386.15 q/ha), dry matter yield (132.90 q/ha), crude protein yield (8.42 q/ha) with higher net return (₹1,17,787/ha) and benefit-cost ratio (4.21) of fodder sorghum during kharif season.